The influence of Korean university students' contact experience with north Korean refugee students on social identity and integrated conflicts / Lee Kyung-Hwa, Kim Seong-Hun and Lee Ga-Hyung - Hwa, Lee Kyung-; Hun, Kim Seong-; Hyung, Lee Ga- (Universiti Teknologi MARA, 2021)
This study investigated the influence of South Korean university students' contact experiences with North Korean refugee university students on social identity and integrated conflicts. The study was conducted with students in years 1-4 of university enrolled in S University in Seoul. Data from 446 participants were gathered. Pearson's correlation analysis was conducted to determine the relationship between college students' contact experience with North Korean defector students, with variables of social identity and integrated conflict included. In addition, a t-test was conducted to analyse the differences in social identities and integrated conflicts according to whether or not college students participated in a unification leadership camp and whether or not they attended lectures related to unification. This study found significant correlations between variables such as contact experience, social identity and integrated conflicts. In addition, an increase in experiences between North Korean defectors and South Korean university students had a positive effect on social identity and negatively affected integrative conflict. In addition, there was no difference in social identity and integrated conflicts according to whether or not students participated in the Unification Camp or attended lectures related to unification. The results of this study will contribute to the development of programs and course openings to increase social identity and reduce integrated conflicts by expanding the contact experience between South and North Korean college students.